Effects of FU Plus tablets on intracavernosal pressure in animal experimentsanimals - Van Anh, Pham Thi; Linh, Do Dieu; Duong, Dau Thuy (Tạp chí Nghiên cứu Y học, 2025)
Erectile dysfunction is defined as the persistent inability to attain and maintain an erection sufficient to permit satisfactory sexual performance, that may affect physical and psychosocial health, and the patients quality of life. A popular trend is to discover and research therapeutic drugs derived from medicinal herbs. FU Plus tablets including Epimedium extract, Tribulus Terrestris Extract, L-Arginine HCl, Red Ginseng extract, Zinc gluconate, Selenium yeast and Yohimbine HCl is a product expected to treat erectile dysfunction. The study was carried out to evaluate the effects of FU Plus tablets on the erectile function through intracavernosal pressure (ICP) in experimental animals. Wistar rats were divided into 3 groups of ten that were given normal saline, sildenafil and FU Plus tablets, respectively. ICP response after cavernous nerve stimulation was recorded. Sildenafil-treated rats and FU Plus-treated rats had shorter response latency, higher peak ICP and longer response duration than untreated control rats. In conclusion, FU Plus tablets have the potential for treating erectile dysfunction.